Experimental study of seismic performance of precast shear wall with a new bolt-plate connection joint. (December 2021) - Li, Wanrun; Gao, Haiwang; Xiang, Rongjiang; Du, Yongfeng
Abstract: Precast shear wall (PSW) have been widely used in structure construction. The connection of the precast part plays an important role in the seismic performance of the PSW. To improve the seismic performance and satisfy various important requirements of the PSW, this paper develops a new bolt-plate connection joint assembled by the high strength bolt with embedded steel plate in the PSW. Experimental study of four shear wall specimens, including one cast-in-situ integral specimen and three PSW specimens with different axial compression ratio, was conducted to investigate the seismic performance of the proposed bolt-plate connection joint under low cyclic loading. The key indexes including horizontal load-lateral displacement curve, skeleton curve, stiffness degradation, strain distribution of connecting device and steel bar are investigated. Results shows that the PSW with the proposed bolt-plate connection joint performed similar failure mode compared to that of the cast-in-situ shear wall (CISSW). The loading-carrying capacity of the PSW with the proposed bolt-plate connection joint is nearly equivalent to that of the CISSW. Note that the proposed connection joint can effectively improve the plastic deformation capacity of the PSW and also enhance the seismic performance and satisfy construction.